ANALISIS PUTUSAN 238/PID,B/2023/PN,GTO TENTANG TINDAK PIDANA PENGGELAPAN DALAM JABATAN - Ibrahim, Nurmila; Radjak, Karmila Damariani; Tahir, Muhammad Rahmat (The Factum Law Review Journal, 2024)
Criminal acts are offences related to cases processed in the Gorontalo District Court, specifically Decision Number 238/Pid.B/2023/PN.Gto, in which the court found the defendant guilty of embezzlement in office, as stipulated in Article 374 of the Criminal Code, and sentenced to two years of imprisonment. This research aims to examine and analyze the judge's considerations regarding the crime of embezzlement in office based on Decision Number 238/Pid.B/2023/PN.Gto and the concept of embezzlement in office as outlined in Article 374. This study utilized legal analysis or legal sources collected to address issues within the research. A qualitative descriptive analysis was employed, involving a description of the research findings using a statutory approach. The research findings indicated that the judge considered the defendant's actions, which violated Article 374 of the Criminal Code concerning embezzlement in office. Sociological considerations included aggravating and mitigating factors, with the judge noting that the defendant had returned the embezzled funds. The sentencing aimed not only to deter the defendant, as the act caused losses to PT Agape Indah Logistik Gorontalo but also to ensure accountability. The defendant was held accountable with a prison sentence of two (2) years based on Article 374 of the Criminal Code. Keywords: Decision Analysis, Embezzlement Crime.